Crafting Effective Captions: Strategies for Enhancing Students’ Engagement and Writing Skill - Sri Wardani (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2023)
This research aims to investigate students' proficiency in writing skills through the utilization of photographs as writing prompts (captions). The study focuses on analyzing the outcomes of students' caption writing using a four-step writing process, namely drafting, revising, editing, and publishing. The assessment involved a caption writing test to evaluate students' progress, supplemented by a questionnaire to gather additional data. The participants consisted of 32 students from XII MIPA 4 of SMA N 1 Malang. Following one cycle of the teaching and learning process, the findings of this research demonstrate that the implementation of the four-step writing process in caption writing enhances students' writing skills and fosters greater student engagement. Specifically, 26 out of the 32 students achieved a score of 75 or higher. The result of sample paired test also shows there is significant difference between before and after the interviention. Consequently, employing the process of caption writing proves to be effective in improving students' writing abilities and promoting increased student engagement.